The influence of tennis motor abilities and anthropometric measures on the competition successfulness of 11 and 12 year-old female tennis players - Filipcic, A.; Filipcic, T. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2005)
A sample of 75 young female tennis players, aged 11 and 12, was included in a research project aimed at establishing the influence of selected anthropometric measures and tennis motor abilities on the competitionsuccessfulness of young tennis players. The selected tennis motor variables include: the muscular power of arms and shoulders, elastic power of the legs, repetitive strength of the trunk, speed of movement, speed of alternative movements with the arm, flexibility of theback,agility,and hand-eye coordination. The results of regression analysis of anthropometric measures reveal a statistically significant connection with the criterion variable (0.36). The system of predictor variables can explain 13% of the variance of the criterion variable. The same applies to tennis motor variables, where the relevant value is somewhat closer, reaching 0.64, while the system of predictors explains 41% of the variance of the criterion variable. Of the anthropometric measures three variables (calf girth, body weight and abdominal /suprailiac/ skinfold) explain the criterion variable with statistical significance. Among the tennis motor variables the above-mentioned variable is represented by the 2400-m run, used for measuring running endurance, and the 5-m run, used for measuring speed of movement.